2009
DOI: 10.1038/nature08611
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating DNA replication by means of priming loop and differential synthesis rate

Abstract: Genomic DNA is replicated by two DNA polymerase molecules: one works in close association with the helicase to copy the leading-strand template in a continuous manner while the second copies the already unwound lagging-strand template in a discontinuous manner through synthesis of Okazaki fragments 1, 2 . Considering the lagging-strand polymerase has to recycle after every Okazaki fragment through the slow steps of primer synthesis and hand-off to the polymerase 3-5 , it is not understood how the two strands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 32 publications
3
113
2
Order By: Relevance
“…In the second model, coordination is achieved by different synthesis rates of the leading and the lagging strands. Contrary to the results described by Lee et al (32), the studies of the T7 replisome by Pandey et al (37) indicated that lagging-strand DNA synthesis is 38% faster than leading-strand DNA synthesis. In addition, no pausing of replisome movement was detected during primer synthesis.…”
Section: And Saxs (5)contrasting
confidence: 54%
“…In the second model, coordination is achieved by different synthesis rates of the leading and the lagging strands. Contrary to the results described by Lee et al (32), the studies of the T7 replisome by Pandey et al (37) indicated that lagging-strand DNA synthesis is 38% faster than leading-strand DNA synthesis. In addition, no pausing of replisome movement was detected during primer synthesis.…”
Section: And Saxs (5)contrasting
confidence: 54%
“…7B). Gp4, translocating in a 5′-3′ direction, encounters a PRS and synthesizes a primer, pausing the replisome while the primer remains bound to gp4 (33)(34)(35) before its transfer to DNA polymerase. In this step, gp2.5 promotes more efficient full-length primer synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent single-molecule experiments have demonstrated the existence of an alternative mechanism to couple primase activity to leading-strand synthesis (72,82). The formation of a small, ssDNA loop between helicase and primase would allow helicase-mediated unwinding to continue while the primase remains bound to the lagging strand to synthesize a primer.…”
Section: Dna Primase Activitymentioning
confidence: 99%
“…It is not well understood how these slow enzymatic steps can take place at the lagging strand without losing coordination with the continuous and fast leadingstrand synthesis (62,93,108). Does the laggingstrand DNA polymerase synthesize faster than the leading-strand DNA polymerase to compensate for the time lost during polymerase cycling (14,82)? Or does leading-strand synthesis transiently halt to prevent it from outpacing lagging-strand synthesis (64)?…”
Section: Dna Primase Activitymentioning
confidence: 99%